Field-based AFDD for refrigerant undercharge in residential HVAC systems: enhancing reliability through false alarm mitigation - Young Jae Choi; Yeobeom Yoon; Piljae Im; Sungkyun Jung; Brian Kolar; Tim Dyer; Youngsik Choi (Energy and Buildings, 2026)

Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Daijun Liu; Franz Essl; Bernd Lenzner; Dietmar Moser; Philipp Semenchuk; Tim M. Blackburn; Phillip Cassey; Dino Biancolini; César Capinha; Wayne Dawson; Ellie E. Dyer; Benoit Guénard; et al. (Global Change Biology, 2024)
The ecological impact of non‐native species arises from their establishment in local assemblages. However, the rates of non‐native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non‐native species and residence of non‐native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non‐native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non‐native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi‐natural ecosystems. Notably, non‐native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land‐use types rather than croplands and urban areas. The impact of residence time on non‐native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land‐use types. The unpredictability of future impacts, implied by the slow spread of non‐native species, strengthens the call for stronger regulations on the exchange of non‐native species to reduce the long‐lasting invasion debt looming on ecosystems' future.

Comparative psychophysics of Western honey bee (Apis mellifera) and stingless bee (Tetragonula carbonaria) colour purity and intensity perception - Sebastian Koethe; Lara Reinartz; Tim A. Heard; Jair E. Garcia; Adrian G. Dyer; Klaus Lunau (Journal of Comparative Physiology A, 2022)
Bees play a vital role as pollinators worldwide and have influenced how flower colour signals have evolved. The Western honey bee, Apis mellifera (Apini), and the Buff-tailed bumble bee, Bombus terrestris (Bombini) are well-studied model species with regard to their sensory physiology and pollination capacity, although currently far less is known about stingless bees (Meliponini) that are common in pantropical regions. We conducted comparative experiments with two highly eusocial bee species, the Western honey bee, A. mellifera , and the Australian stingless bee, Tetragonula carbonaria , to understand their colour preferences considering fine-scaled stimuli specifically designed for testing bee colour vision. We employed stimuli made of pigment powders to allow manipulation of single colour parameters including spectral purity (saturation) or colour intensity (brightness) of a blue colour (hue) for which both species have previously shown innate preferences. Both A. mellifera and T. carbonaria demonstrated a significant preference for spectrally purer colour stimuli, although this preference is more pronounced in honey bees than in stingless bees. When all other colour cues were tightly controlled, honey bees receiving absolute conditioning demonstrated a capacity to learn a high-intensity stimulus significant from chance expectation demonstrating some capacity of plasticity for this dimension of colour perception. However, honey bees failed to learn low-intensity stimuli, and T. carbonaria was insensitive to stimulus intensity as a cue. These comparative findings suggest that there may be some common roots underpinning colour perception in bee pollinators and how they interact with flowers, although species-specific differences do exist.

Competition and pollen wars: simulations reveal the dynamics of competition mediated through heterospecific pollen transfer by non-flower constant insects - Alan Dorin; Tim Taylor; Martin Burd; Julian Garcia; Mani Shrestha; Adrian G. Dyer (Theoretical Ecology, 2021)

Evidence for Rapoport’s rule and latitudinal patterns in the global distribution and diversity of alien bird species - Ellie E. Dyer; David W. Redding; Phillip Cassey; Ben Collen; Tim M. Blackburn (Journal of Biogeography, 2020)
Aim To quantify global latitudinal patterns in the distributions of alien bird species to assess whether these species conform to Rapoport's rule (i.e. show a positive latitudinal gradient in latitudinal range extent), and to test whether where species are introduced, and where species fail to establish, may help to drive observed patterns. Location Global. Taxon Birds (group Aves). Methods Data on locations of introduction and establishment for 355 species with established alien populations were combined with data on native range extents (measured in 5° bands of latitude). Relationships between (a) latitude and introduced and established alien species richness, and (b) latitude and introduced and established alien range extent, were plotted. Linear regressions and paired t ‐tests were used to compare latitudinal range extents, midpoints, and limits of each species in its introduced alien range, established alien range and native range. Results Latitudes that have more established alien bird species also have had more species introduced in total. The mean total latitudinal extents (i.e. geographic range size) of established alien bird species increase with latitude poleward of the tropics, consistent with Rapoport's rule, but are smaller in the tropics. This pattern is weaker in the range sizes of native bird species. Alien bird species are more likely to be introduced within the latitudinal confines of their native ranges, and are more likely to contract away from the more extreme latitudes to which they were introduced. Alien bird species are in general more likely to have established populations nearer the equator. Main conclusions Including data on locations of introduction in addition to established distributions enables us to determine the extent to which large‐scale alien species distributions are determined by anthropogenic or natural processes. Latitudinal patterns in range extent (Rapoport's rule) and species richness in alien birds are largely a consequence of where species have been introduced, and hence are unlikely to be informative of equivalent patterns in native species.

Species invasions and the phylogenetic signal in geographical range size - Alex L. Pigot; Ellie E. Dyer; David W. Redding; Phillip Cassey; Gavin H. Thomas; Tim M. Blackburn (Global Ecology and Biogeography, 2018)
Aim Accelerating rates of anthropogenic introductions are leading to a dramatic restructuring of species distributions globally. However, the extent to which invasions alter the imprint of evolutionary history in species geographical ranges remains unclear. Here, we provide a global assessment of how the introduction, establishment and spread of alien species alters the phylogenetic signal in geographical range size using birds as a model system. Location Global. Time period Contemporaneous. Taxa Birds. Methods We compare the phylogenetic signal in alien range size with that of native distributions of species globally ( n = 9,993) and across different stages in the invasion pathway, from introduced ( n = 965) to established species ( n = 359). Using stochastic simulations, we test whether differences in phylogenetic signal arise from nonrandom patterns of species introduction, establishment or spread. Results Geographical range size in birds exhibits an intermediate phylogenetic signal, driven by the spatial clustering of closely related species. Nonrandom introductions, biased towards wide‐ranging species from particular clades and regions, produce an anomalously strong phylogenetic signal in the native range size of introduced species. In contrast, the phylogenetic signal in alien range size is substantially weaker than for native distributions. This weak phylogenetic signal cannot be explained by a lack of time for dispersal but is instead regulated by phylogenetic correlations across species in the location and number of introduction events. Main conclusions We demonstrate that the effects of anthropogenic introductions on the phylogenetic signal in range size vary across different stages in the invasion pathway. The process of transport and introduction amplifies the phylogenetic signal in the pool of potential invaders, whereas the subsequent pattern of spread decouples variation in alien range size from phylogenetic ancestry. Together, our findings suggest that evolutionary relatedness is likely to be a relatively weak predictor of the spread of invasive species.

A global analysis of the determinants of alien geographical range size in birds - Ellie E. Dyer; Victoria Franks; Phillip Cassey; Ben Collen; Robert C. Cope; Kate E. Jones; Çagan H. Şekercioğlu; Tim M. Blackburn (Global Ecology and Biogeography, 2016)
Aim Determining the causes of range size variation in the distributions of alien species is important for understanding the spread of invasive species. Factors influencing alien range size have been explored for some species at a regional level, but to date there has been no global analysis of an entire class. Here, we present such an analysis for birds, testing for the effects of introduction event, location and species‐level variables on alien range sizes. Location Global. Methods We used a novel dataset on the global distributions of alien bird species to test for relationships between alien range size and colonization pressure, residence time, extent of the global climatic niche, native range size, body mass and specialization, using a statistical approach based on phylogenetic generalized least squares models. We performed this analysis globally, and for separate biogeographical realms. Results Approximately half of the variation in alien bird range size is explained by colonization pressure in univariate analysis. We identified consistent effects of higher colonization pressure at global and realm levels, as well as support for effects of native range size and residence time. We found less support for effects of body mass, specialization or extent of the global climatic niche on alien range size. Main conclusions Alien bird range sizes are generally small relative to their native range sizes, and many are continuing to expand. Nevertheless, current variation is predictable, most strongly by the event‐level factor of colonization pressure. Whether a species is widespread is a better predictor of alien range size than whether a species could be widespread (estimated by global climatic niche extent), while we also find effects of residence time on alien range size. These relationships may help to identify those alien species that are more likely to spread and hence have greater environmental and economic impacts where they have been introduced.

Long after the event, or four things we (should) know about bird invasions - Tim M. Blackburn; Ellie Dyer; Shan Su; Phillip Cassey (Journal of Ornithology, 2015)